Comparative transcriptome analysis revealed molecular mechanisms of peanut leaves responding to Ralstonia solanacearum and its type III secretion system mutant - Yang, Yong; Chen, Ting; Dai, Xiaoqiu; Yang, Dong; Wu, Yushuang; Chen, Huilan; Zheng, Yixiong; Zhi, Qingqing; Wan, Xiaorong; Tan, Xiaodan (Frontiers in Microbiology, 2022)
Bacterial wilt caused by Ralstonia solanacearum is a serious soil-borne disease that limits peanut production and quality, but the molecular mechanisms of the peanut response to R. solanacearum remain unclear. In this study, we reported the first work analyzing the transcriptomic changes of the resistant and susceptible peanut leaves infected with R. solanacearum HA4-1 and its type III secretion system mutant strains by cutting leaf method at different timepoints (0, 24, 36, and 72 h post inoculation). A total of 125978 differentially expressed genes (DEGs) were identified and subsequently classified into six groups to analyze, including resistance-response genes, susceptibility-response genes, PAMPs induced resistance-response genes, PAMPs induced susceptibility-response genes, T3Es induced resistance-response genes, and T3Es induced susceptibility-response genes. KEGG enrichment analyses of these DEGs showed that plant-pathogen interaction, plant hormone signal transduction, and MAPK signaling pathway were the outstanding pathways. Furter analysis revealed that CMLs/CDPKs-WRKY module, MEKK1-MKK2-MPK3 cascade, and auxin signaling played important roles in the peanut response to R. solanacearum. Upon R. solanacearum infection, three early molecular events were possibly induced in peanuts, including Ca2+ activating CMLs/CDPKs-WRKY module to regulate the expression of resistance/susceptibility-related genes, auxin signaling was induced by AUX/IAA-ARF module to activate auxin-responsive genes that contribute to susceptibility, and MEKK1-MKK2-MPK3-WRKYs was activated by phosphorylation to induce the expression of resistance/susceptibility-related genes. Our research provides new ideas and abundant data resources to elucidate the molecular mechanism of the peanut response to R. solanacearum and to further improve the bacterial wilt resistance of peanuts.